Direct-infusion electrospray ionization-mass spectrometry analysis reveals atractyligenin derivatives as potential markers for green coffee postharvest discrimination. (April 2019) - Tsukui, Anna; Vendramini, Pedro H.; Garrett, Rafael; Scholz, Maria Brígida S.; Eberlin, Marcos N.; Bizzo, Humberto R.; Rezende, Claudia M.
Abstract: Coffee quality is strongly related to postharvest processes. Dry and wet are the most traditional and employed processes. However, more recently, the semi-dry process has been introduced and applied for producing coffees of good quality in a more environmental friendly manner compared to the wet process. In this work, green Arabica coffee cherries from two consecutive crops were submitted to the dry and semi-dry postharvest processes and their methanol:water extracts were characterized by ESI(−) FT-ICR MS followed by chemometric data analysis. Thirty-three compounds were identified in the extracts by their high-resolution and accurate m/z values and MS/MS spectra being nine of them diterpenes related to atractyligenin derivatives. The dry and semi-dry processes led to distinct extracts in which compounds such as atractyloside II, carboxyatractyloside II and carboxyatractyloside III showed the greatest contributions (p < 0.05) based on t -Student's test and PLS-DA statistical analyses. These compounds were able to discriminate the postharvest processes for coffees from two consecutive crops. These results can help to better understand the effects of the postharvest processes in the final chemical composition and coffee quality. Highlights: ESI(−)FT-ICR MS profile was able to differentiate postharvest processes of coffee. Natural and pulped natural coffees were discriminated by data analysis of two crops. Glycosylated diterpenes were the main compounds responsible for the differentiation.